Growth and Foliage Nutrients Evaluation of Dendrocalamus strictus Roxb. From Himachal Pradesh and Punjab Plains - Chauhan, V. K.; Thakur, Vidhya (Indian Forester, 2003)
Forty two Candidate Plus Clumps (CPCs) were selected from the entire range of distribution in Himachal Pradesh and Punjab plains for growth and foliage nutrients evaluation at two different sites. Results were significant for growth attributes and foliage nutrients. Significantly higher growth variation in height, DBH of culm, number of internodes, branch length, number ofleaveslbranch, new culms/clump and nutritional content in foliage was recorded in selection SRB-l, followed by SRM-3 and SRK-2 at both sites of evaluation as compared to the minimum values in PKB-19 at S1 and H.S.S. 21 at S2.